Non steroidal anti-inflammatory drugs in the prevention of cystoid macular edema after uneventful cataract surgery - Quintana NE (Dove Medical Press, 2014)
Nicolás E Quintana,* Alejandro R Allocco,* Julia A Ponce,* Mauricio GB Magurno Instituto Santa Lucía, Paraná, Argentina *These authors contributed equally to this work Background: Cystoid macular edema (CME) remains an important complication after cataract surgery. There is no consensus about how to prevent this frequent complication. The purpose of this study was to conceive an effective anti-inflammatory strategy using nonsteroidal anti-inflammatory drugs (NSAIDs) together with regular treatment with corticosteroids to prevent CME and improve visual acuity after cataract surgery in patients without risk factors. Materials and methods: We searched the PubMed, Cochrane, and Google Scholar databases focused on prospective, controlled, randomized, double-blind clinical trials published in the last 10 years, with a minimum follow-up of 4 weeks. Results: A total of nine clinical trials, one systematic review, and two reviews satisfied our search criteria. Most studies highlighted that NSAIDs are as powerful as corticosteroids to diminish postoperative inflammation, and demonstrated an additional benefit when used in combination with standard corticosteroid postsurgical therapy. In addition, the use of NSAIDs in the perioperative period seems to significantly improve the outcome after surgery and helps prevent CME in low-risk patients. Conclusion: The prophylactic use of NSAIDs in combination with the standard postoperative steroid scheme appears to be a positive course of action for preventing CME after cataract surgery. We suggest a therapeutic scheme based on the administration of one drop four times a day, beginning the day before surgery and for 4 weeks after the procedure. It is also advisable to administer one drop every 15 minutes in the hour prior to surgery in order to obtain better anti-inflammatory efficacy. Keywords: cystoid macular edema, non-steroidal anti-inflammatory drugs, cataract surgery, NSAIDs, CME